Efektivitas Ekstrak Daun Pacar Air (Impatiens balsamina L.) Untuk Meningkatkan Respon Imun Non Spesifik Ikan Nila (Oreochromis niloticus) - Pasaribu, Wesly; Longdong, Sammy N.J (Universitas Sam Ratulangi, 2015)
The objective of this research was to determine the most effective dose and the best induction time of Impatiens balsamina extract in enhancing nonspesific immune response of nile tilapia (Oreochromis niloticus). The tested fish were nile tilapia, 14-16 cm in length, and 39-42 g in weight, obtained from Balai Pengembangan dan Pembinaan Pembudidayaan Ikan (BP3I) Tateli. The research was designed in 2x4 factorial in completely randomized design. There were two factors tested in this research, the dose and time. There were four levels of dose, A1 = 0 mg/mL extract, A2= 30 mg/mL extract, A3= 50 mg/mL extract, A4= 70 mg/mL extract; and there were two levels of time, B1= 7 days after injection and B2=14 days after injection. The extract was injected intramuscularly with a dose of 0.2 mL per fish. Data collected in this research was the immune parameters (total leucocyte count and phagocytosis activity). The results showed that the most effective dose in enhancing nonspesific immune response was A1=50 mg/mL extract and the best induction time was B1= 7 day after injection. The results also indicated that there was significant interaction between dose and time in influencing the total amount of leucocyte, but there was not interaction in influencing the phagocytic activities. Keywords : Impatiens balsamina, immune Response, total leucocyte count, phagocytosis activity.